2016
DOI: 10.1002/cnma.201600198
|View full text |Cite
|
Sign up to set email alerts
|

Monodispersed CuCo Nanoparticles Supported on Diamine‐Functionalized Graphene as a Non‐noble Metal Catalyst for Hydrolytic Dehydrogenation of Ammonia Borane

Abstract: Monodispersed non‐noble CuCo nanoparticles (diameter≤2.4 nm) have been immobilized on diamine‐functionalized reduced graphene oxide, which displays remarkably enhanced catalytic performance for the dehydrogenation of ammonia borane (AB) with a corresponding turnover frequency (TOF) as high as 51.5±3.7 molH2 molcat−1 min−1 at 303 K, compared to those on other supports such as reduced graphene oxide, Vulcan XC‐72R and polyvinypyrrolidone. The synergic effect between Cu and Co could efficiently improve the cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…So, it is necessary to employ suitable support to disperse the metal nanoparticles. Currently, many materials have been adopted as supports including carbon black, graphene, polymers, hydroxyapatites, and zeolites, etc. Recently, chitosan (CS) has received much attention because of its outstanding advantages such as good biocompatibility, biodegradability, nontoxicity, and availability.…”
Section: Introductionmentioning
confidence: 99%
“…So, it is necessary to employ suitable support to disperse the metal nanoparticles. Currently, many materials have been adopted as supports including carbon black, graphene, polymers, hydroxyapatites, and zeolites, etc. Recently, chitosan (CS) has received much attention because of its outstanding advantages such as good biocompatibility, biodegradability, nontoxicity, and availability.…”
Section: Introductionmentioning
confidence: 99%
“…According to the compilation results in Table 2 and Figure 3, it is clear that the combination of different non-noble metals to form metal alloys can also be efficiently applied to dehydrogenation from the hydrolysis of NaBH 4 or NH 3 BH 3 solution, [48][49][50][51][52][53][54] particularly when the alloys are supported on carbon materials, [55][56][57][58][59][60][61][62][63][64] BN, [65][66][67] TiO 2 , [68][69][70] SiO 2 , [15] and MOF. [71][72][73] For instance, Cui et al [55] reported a series of NiFe NPs with N-doped carbon coating anchored on graphene (Ni 2Àx Fe x @CN-G) via thermal pyrolysis.…”
Section: Non-noble Metal Alloysmentioning
confidence: 99%
“…As far as we know, CuCo 2 O 4 nanoplatelets have not been reported yet in the literature. In AB hydrolysis, those nanoplatelets exhibited ultrahigh catalytic activity with turnover frequency (TOF) of 73.4 mol hydrogen min −1 mol cat −1 , which is higher than those of CoP nanoparticles (72.7 mol hydrogen min −1 mol cat −1 ) [22], Cu 0.8 Co 0.2 O/Graphene oxide (70.0 mol hydrogen min −1 mol cat −1 ) [23], Ni 0.9 Mo 0.1 /graphene (66.7 mol hydrogen min −1 mol cat −1 ) [24], CuCo/diamine-functionalized reduced graphene oxide 51.5 mol hydrogen min −1 mol cat −1 ) [25], NiCo 2 O 4 /Ti (50.1 mol hydrogen min −1 mol cat −1 ) [12], CoP nanoarray (42.8 mol hydrogen min −1 mol cat −1 ) [26], Co/CTF(42.3 mol hydrogen min −1 mol cat −1 ) [27], Ni nanoparticles supported on three-dimensional N-doped graphene (41.7 mol hydrogen min −1 mol cat −1 ) [28], CuCo@MIL-101(19.6 mol hydrogen min −1 mol cat −1 ) [29], and CoNi/Graphene (16.8 mol hydrogen min −1 mol cat −1 ) [30], However, this TOF value is still lower than that of Cu 0.6 Ni 0.4 Co 2 O 4 nanowires (119.5 mol hydrogen min −1 mol cat −1 ) [2], Ni/ZIF-8 nanocatalyst (85.7 mol hydrogen min −1 mol cat −1 ) [31], and CuCo/g-C 3 N 4 -1(75.1 mol hydrogen min −1 mol cat −1 ) [32]. In the viscosity range from 1.08 to 32.95 mPa·s, high viscosity has a negative effect on AB hydrolysis.…”
Section: Introductionmentioning
confidence: 99%